Densifying to upgrading: strategies for improving the social hosing built stock in Italy - Ernesto Antonini; Jacopo Gaspari; Giulia Olivieri (Techne, 2012)
The world economic crisis has further depressed the Italian production of social housing but it dramatically increased the demand of affordable rental dwellings. A refurbishment and retrofitting campaign of the social housing stock appears to be as a credible and effective strategy, able to be applied in the short term to bring this gap, at least partially. Some results of a research in progress on the topic are presented in this paper. The first one is a classification model of the main typology of retrofitting and densification of social housing projects, issued from an investigation on several European case-studies. On this base, the research established a set of design criteria, able to couple the improvement of energy, functionality and comfort performances with the increasing of the use intensity of the built stock. Finally, an application of this method on a pilot-case is described.